2019
DOI: 10.5194/bg-16-2693-2019
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter at the fluvial–marine transition in the Laptev Sea using in situ data and ocean colour remote sensing

Abstract: River water is the main source of dissolved organic carbon (DOC) in the Arctic Ocean. DOC plays an important role in the Arctic carbon cycle, and its export from land to sea is expected to increase as ongoing climate change accelerates permafrost thaw. However, transport pathways and transformation of DOC in the land-to-ocean transition are mostly unknown. We collected DOC and a CDOM (λ) samples from 11 expeditions to river, coastal and offshore waters and present a new DOC-a CDOM (λ) model for the fluvial-mar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 71 publications
(136 reference statements)
3
38
0
Order By: Relevance
“…However, since our media has been kept in dark during the whole experiment, the S r values in this study relate to the composition of CDOM rather than processing. In addition, it has been shown that lower spectral slopes in the UVA area for Arctic coastal water is not correlated with photodegradation (Juhls et al, 2019), and that the lower spectral slope for UVA instead likely reflects lability of DOM (Matsuoka et al, 2015). Therefore, we conclude that the significant differences in S r values between the three glacial deposit types underline differences in the DOM composition.…”
Section: Characteristics Of Dom In Mediamentioning
confidence: 65%
“…However, since our media has been kept in dark during the whole experiment, the S r values in this study relate to the composition of CDOM rather than processing. In addition, it has been shown that lower spectral slopes in the UVA area for Arctic coastal water is not correlated with photodegradation (Juhls et al, 2019), and that the lower spectral slope for UVA instead likely reflects lability of DOM (Matsuoka et al, 2015). Therefore, we conclude that the significant differences in S r values between the three glacial deposit types underline differences in the DOM composition.…”
Section: Characteristics Of Dom In Mediamentioning
confidence: 65%
“…Note that we do not include additional terrigenous sources of CDOM and suspended material. Depending on the region (Stedmon et al, 2011) and the time of the year (Juhls et al, 2020), we may underestimate CDOM absorption locally by up to an order of 10 times, compared to measured values (Heim et al, 2014; Juhls et al, 2019; Soppa et al, 2019). By accounting for the loading of major Arctic rivers, its effect is expected to be larger than shown here.…”
Section: Implications and Conclusionmentioning
confidence: 90%
“…Hydrological flow paths will shift toward increased groundwater flow and affect the source and composition of dissolved organic matter (DOM) (Amon et al, 2012). While particulate material is mostly deposited in shelf sea sediments to become mineralised or buried (Charkin et al, 2011;Wegner et al, 2013), dissolved organic matter is exported offshore into the open Arctic Ocean (i.e., Juhls et al, 2019) and approximately 50% is thought to be exported onwards to the Atlantic (Granskog et al, 2012). Most of the DOM transported by the Lena River originates from leaching of surface soils of dominantly boreal forest vegetation (Amon et al, 2012;Kaiser et al, 2017).…”
Section: Introductionmentioning
confidence: 99%